Best practices for the management of local-regional recurrent chordoma: a position paper by the Chordoma Global Consensus Group - Stacchiotti, S.; Gronchi, A.; Fossati, P.; Akiyama, T.; Alapetite, C.; Baumann, M.; Blay, J.Y.; Bolle, S.; Boriani, S.; Bruzzi, P.; Capanna, R.; Caraceni, A.; et al. (Annals of oncology, 2017)
Chordomas are rare, malignant bone tumors of the skull-base and axial skeleton. Until recently, there was no consensus among experts regarding appropriate clinical management of chordoma, resulting in inconsistent care and suboptimal outcomes for many patients. To address this shortcoming, the European Society of Medical Oncology (ESMO) and the Chordoma Foundation, the global chordoma patient advocacy group, convened a multi-disciplinary group of chordoma specialists to define by consensus evidence-based best practices for the optimal approach to chordoma. In January 2015, the first recommendations of this group were published, covering the management of primary and metastatic chordomas. Additional evidence and further discussion were needed to develop recommendations about the management of local-regional failures. Thus, ESMO and CF convened a second consensus group meeting in November 2015 to address the treatment of locally relapsed chordoma. This meeting involved over 60 specialists from Europe, the United States and Japan with expertise in treatment of patients with chordoma. The consensus achieved during that meeting is the subject of the present publication and complements the recommendations of the first position paper.